The Effect of Learning Literature Through Movies on EFL Learner's Analytical Thinking and Interest in Literature - DJEDID Oulfa. (My University, 2026)
Abstract In many EFL contexts, students often experience difficulties in studying literature because literary texts may appear complex, abstract, and less engaging, which can negatively affect their motivation and classroom participation. Therefore, the present study investigated the effect of learning literature through movies on EFL students’ analytical thinking skills and their interest in literature. Therefore, a mixed-methods research design was adopted involving 36 third-year EFL students at Mohammed Cherif Messaadia University in Souk Ahras. The participants were divided into an experimental group, which studied literature through films, and a control group that followed the traditional method.Data were collected through an analytical thinking pre-test and post-test, a questionnaire, and a semi-structured interview. The findings revealed that the use of movies positively contributed to improving students’ analytical thinking skills and increasing their interest in literature. Students also showed positive attitudes toward film-based learning and considered it more engaging and accessible. Overall, the study concludes that integrating movies into literature teaching can be an effective pedagogical approach for creating a more interactive and student-centred learning environment. ------------------------------ ملخص في العديد من سياقات تعلم اللغة الإنجليزية كلغة أجنبية، يواجه الطلبة صعوبات في دراسة الأدب، إذ قد تبدو النصوص الأدبية معقدة ومجردة و غير مشوقة، مما قد يؤثر سلبًا على دافعيتهم ومشاركتهم داخل الصف. لذلك، هدفت هذه الدراسة إلى بحث أثر تعلم الأدب من خلال الأفلام على مهارات التفكير التحليلي واهتمام طلبة الإنجليزية كلغة أجنبية بالأدب. ولتحقيق هذا الهدف، تم اعتماد المنهج المختلط بمشاركة 36 طالبًا من طلبة السنة الثالثة تخصص لغة إنجليزية بجامعة محمد الشريف مساعدية بسوق أهراس، حيث تم تقسيم المشاركين إلى مجموعتين: مجموعة تجريبية درست الأدب من خلال الأفلام، ومجموعة ضابطة درست بالطريقة التقليدية. وتم جمع البيانات باستخدام اختبار قبلي وبعدي للتفكير التحليلي، واستبيان، ومقابلة شبه موجهة. وأظهرت النتائج أن استخدام الأفلام ساهم بشكل إيجابي في تحسين مهارات التفكير التحليلي لدى الطلبة وزيادة اهتمامهم بالأدب. كما عبّر الطلبة عن اتجاهات إيجابية نحو التعلم القائم على الأفلام واعتبروه أكثر تشويقًا وسهولة في الفهم. وبشكل عام، خلصت الدراسة إلى أن دمج الأفلام في تدريس الأدب يُعد مقاربة بيداغوجية فعّالة تسهم في خلق بيئة تعليمية أكثر تفاعلاً وتركيزًا على الطالب ------------------ Résumé Dans de nombreux contextes d’apprentissage de l’anglais langue étrangère (EFL), les étudiants rencontrent souvent des difficultés dans l’étude de la littérature, car les textes littéraires peuvent paraître complexes, abstraits et peu motivants, ce qui peut affecter leur participation et leur intérêt. Par conséquent, cette étude vise à examiner l’effet de l’apprentissage de la littérature à travers les films sur les compétences de pensée analytique des apprenants EFL ainsi que sur leur intérêt pour la littérature. Afin d’atteindre cet objectif, une méthodologie mixte a été adoptée auprès de 36 étudiants de troisième année d’anglais à l’Université Mohamed Chérif Messaadia de Souk Ahras. Les participants ont été répartis en deux groupes : un groupe expérimental ayant étudié la littérature à travers les films et un groupe témoin ayant suivi une méthode traditionnelle. Les données ont été recueillies à l’aide d’un pré-test et d’un post-test de pensée analytique, d’un questionnaire ainsi que d’un entretien semi-directif. Les résultats ont révélé que l’utilisation des films a contribué positivement à l’amélioration des compétences de pensée analytique des étudiants ainsi qu’à l’augmentation de leur intérêt pour la littérature. Les étudiants ont également exprimé des attitudes positives envers l’apprentissage basé sur les films et l’ont considéré comme plus motivant et plus accessible. Dans l’ensemble, l’étude conclut que l’intégration des films dans l’enseignement de la littérature constitue une approche pédagogique efficace favorisant un environnement d’apprentissage plus interactif et centré sur l’étudiant
Keywords: : Analytical thinking; film-based learning; EFL learners; movies; Interest in literature.; طلبة الإنجليزية كلغة أجنبية، تدريس الأدب، الأفلام، التفكير التحليلي، الاهتمام بالأدب، التعلم القائم على الأفلام، التحليل الأدبي.; apprenants EFL; enseignement de la littérature; films; pensée analytique; intérêt pour la littérature; apprentissage basé sur les films